1993
DOI: 10.1007/bf00271376
|View full text |Cite
|
Sign up to set email alerts
|

Influence of usual intake of dietary caffeine on single-dose kinetics of theophylline in healthy human subjects

Abstract: The influence of usual multiple ingestions of dietary caffeine on oral single-dose pharmacokinetics of theophylline has been investigated in 6 healthy male subjects. The subjects consumed 2 to 7 cups of regular instant coffee during the 24 h study period. Their mean serum concentrations of caffeine varied from 1.2 to 3.1 mg/l. After their usual intake of dietary caffeine, the serum concentrations of theophylline from 3 to 24 h after administration were significantly higher than after deprivation of dietary caf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The greatest effect was observed in patients who were heavy smokers (40 cigarettes per day) . Concomitant caffeine and theophylline ingestion also reduced the elimination of both compounds …”
Section: Medicinal Chemistry Of Caffeinementioning
confidence: 94%
See 1 more Smart Citation
“…The greatest effect was observed in patients who were heavy smokers (40 cigarettes per day) . Concomitant caffeine and theophylline ingestion also reduced the elimination of both compounds …”
Section: Medicinal Chemistry Of Caffeinementioning
confidence: 94%
“…76 Concomitant caffeine and theophylline ingestion also reduced the elimination of both compounds. 77 2.2. Molecular Activities of Caffeine.…”
Section: Medicinal Chemistry Of Caffeinementioning
confidence: 99%
“…It has been reported that caffeine consumption might influence the pharmacokinetics of drugs which are substrates of CYP1A2 (Sato et al 1993; Vainer & Chouinard 1994) and, accordingly, our recent data indicated that caffeine increases the bioavailability of melatonin by 120% due to inhibition of melatonin first‐pass metabolism without significant effect on the elimination half‐life (Härter et al 2003). Thus, dietary caffeine intake could be a potential confounder when melatonin is used for CYP1A2 phenotyping.…”
mentioning
confidence: 99%
“…Inhibitors of CYP1A2 increase serum caffeine concentration (Carrillo & Benítez 2000), and caffeine itself may act as a CYP1A2 inhibitor. In an open cross‐over trial, caffeine‐containing instant coffee at 2 to 7 cups per day reduced the clearance of CYP1A2 substrate theophylline by 23% (Sato et al 1993).…”
mentioning
confidence: 99%